PHYSICOCHEMICAL AND MICROBIOLOGICAL QUALITY OF THE WATERS OF THE YAQUE NORTE RIVER, DOMINICAN REPUBLIC - Lemus, Mairin Josefina (2022)
The Yaque Norte is one of the most important rivers in the Dominican Republic, it is used for consumption purposes, reserve dams, hydroelectric plants, irrigation and others; however, the evidence shows that many of the domestic and industrial effluents are discharged directly into its waters, without prior treatment. In the present work, a physicochemical and microbiological evaluation of surface waters in the upper, middle and lower basin of the Yaque del Norte River is carried out, using the Standard Methods for water analysis. The results show that there are no significant differences in the physicochemical parameters: pH, salinity, conductivity, turbidity, total solids and hardness; however, these parameters show alterations along the river. The levels of total coliforms, fecal or thermotolerant coliforms and Escherichia coli exceed the limits established in the Dominican regulation. The water does not meet standards for consumption and this represents a major environmental and health problem for the communities surrounding the river that use it.